Water droplet bouncing on a non-superhydrophobic Si nanospring array. Issue 3 (24th December 2020) - Kumar, Samir; Namura, Kyoko; Suzuki, Motofumi; Singh, Jitendra P.
Abstract : Water droplets striking non-superhydrophobic thin films of silicon nanosprings do not wet the surface but rebound. Abstract : Self-cleaning surfaces often make use of superhydrophobic coatings that repel water. Here, we report a hydrophobic Si nanospring surface that effectively suppresses wetting by repelling water droplets. The dynamic response of Si nanospring arrays fabricated by glancing-angle deposition is investigated. These hydrophobic arrays of vertically standing nanosprings (about 250 nm high and 60 nm apart) allow the droplets to rebound within a few milliseconds after contact. Amazingly, the morphology of the nanostructures influences the impact dynamics. The rebound time and coefficient of restitution are higher for Si nanosprings than for vertical Si columns. By considering the droplet/nanospring surface as a coupled-spring system, we argue that the restoring force of the nanosprings may be responsible for the water-droplet rebound. The bouncing phenomena studied here are essential in the design of self-cleaning surfaces and are also of fundamental importance for the study of wetting behavior on nanostructures.